Presidential Control over Administration : A New Historical Analysis of Public Finance Policymaking, 1929-2018 - O'Brien, Patrick R. (Book collections on Project MUSE., 2022)
"The United States Constitution recognizes the president as the sole legal head of the executive branch and thus the one in charge of the administration. Despite this constitutional authority, the president's actual control over administration varies significantly in practice from one president to the next. Through extensive empirical analysis, Patrick O'Brien argues that presidential control over administration operates as a historical variable and functions as a key component of policymaking. To explain the different configurations of presidential control that recur throughout history and to test the argument, this book develops a new theory and then traces the policymaking process in the domain of public finance across nearly a century of history, beginning with the Great Depression and ending with the first two years of the Trump presidency. O'Brien shows that the initial efforts of Obama and Trump to change the established course during a period of unified party control of the government were largely undercut-or "effectively blocked," respectively-by their own limited control over administration. Due to factors such as time, knowledge, government structure, and incentives, O'Brien demonstrates that presidential control over administration conforms to four configurations that recur in succession: collapse, innovation, stabilization, and constraint. He then shows how these configurations played out in the New Deal, Reagan, and Great Recession eras, thus providing readers with an empirically tested theory for how unilateral and legislative policymaking differs over time. Presidential Control over Administration is a groundbreaking contribution to our understanding of the presidency and policymaking"--